2018
DOI: 10.31083/jin-170058
|View full text |Cite
|
Sign up to set email alerts
|

Neural activation patterns and connectivity in visual attention during Number and Non-number processing: An ERP study using the Ishihara pseudoisochromatic plates

Abstract: Visual cognitive function is important in the construction of executive function in daily life. Perception of visual number form (e.g. Arabic digits) and numerosity (numeric magnitude) is of interest to cognitive neuroscientists. Neural correlates and the functional measurement of number representations are complex events when their semantic categories are assimilated together with concepts of shape and color. Color perception can be processed further to modulate visual cognition. The Ishihara pseudoisochromat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Colour-related neuropsychology tests include the Weigl Colour-Form Sorting Test, the Wisconsin Card Sorting Test, and the Stroop Test [14][15][16] . The Ishihara colour chart has been used to detect colour perception deficiency 17 , and another study concluded that attention deficits and brain connectivity disorders can be determined using the Ishihara colour chart 18 . However, all event-related potential (ERP) studies on colours focused on different types of ERP components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Colour-related neuropsychology tests include the Weigl Colour-Form Sorting Test, the Wisconsin Card Sorting Test, and the Stroop Test [14][15][16] . The Ishihara colour chart has been used to detect colour perception deficiency 17 , and another study concluded that attention deficits and brain connectivity disorders can be determined using the Ishihara colour chart 18 . However, all event-related potential (ERP) studies on colours focused on different types of ERP components.…”
Section: Resultsmentioning
confidence: 99%
“…However, all event-related potential (ERP) studies on colours focused on different types of ERP components. For example, the N200 and P300 ERP components have focused on attention 4,5 and brain connectivity 18 , but no study has yet detected and analysed perception processing of colour. Among ERP components, the C1 ERP component can explain visual perception.…”
Section: Resultsmentioning
confidence: 99%